Straw Cover and Tire Model Effect on Soil Stress - Filho, Aldir Carpes Marques; Santana, Lucas Santos; Martins, Murilo Battistuzzi; da Silva Guimarães Júnnyor, Wellingthon; de Medeiros, Simone Daniela Sartório; Lanças, Kléber Pereira [UNESP] (MDPI, 2025)
Heavy machinery degrades agricultural soils, with severity influenced by wheel type, contact area, and soil moisture. Tropical agriculture is characterized by the constant maintenance of straw on the ground. This permanent cover, among other benefits, can mitigate the stress imposed by wheels on the physical structure of the soil. This study aimed to evaluate the effect of tire types and straw amounts on soil stresses. Static studies were carried out under controlled conditions in a static tire test unit (STTU), equipped with standardized sensors and systems that simulated real farming conditions. Three tire models were tested: road truck double wheelset—2 × 275/80R22.5 (p1); agricultural radial tire—600/50R22.5 (p2); and bias-ply tire—600/50-22.5 (p3) on four contact surfaces (rigid surface; bare soil; soil with 15 and 30 Mg ha−1 straw cover). We performed comparative statistical tests and subsurface stress simulations for each tire and surface condition. On the hard surface, the contact areas were 4.7 to 6.8 times smaller than on bare soil. Straw increased the tire’s contact area, reducing compaction and subsoil stresses. Highest pressure was imposed by the road tire (p1) and lowest by the radial tire (p2). Adding 15 Mg ha−1 of straw reduced soil SPR by 18%, while increasing it to 30 Mg ha−1 led to an additional 8% reduction. Tire selection and effective straw management improve soil conservation and agriculture sustainability.